Standard specification for high-strength low-alloy structural steel. (American Society for Testing and Materials, 2009)
This specification covers high-strength low-alloy structural steel shapes, plates, and bars for welded, riveted, or bolted construction intended primarily for use as structural members where savings in weight [mass] or added durability are important. The atmospheric corrosion resistance of the steel in most environments is substantially better than that of carbon structural steels with or without copper addition. When properly exposed to the atmosphere, this steel can be used bare (unpainted) for many applications (see Note 1). This specification is limited to material up to 4 in. [100 mm], inclusive, in thickness.